2010
DOI: 10.14214/sf.143
|View full text |Cite
|
Sign up to set email alerts
|

Harvesting alternatives, accumulation and procurement cost of small-diameter thinning wood for fuel in Central Finland

Abstract: This study compared harvesting alternatives, accumulation and procurement costs of smalldiameter thinning wood chips for fuel, when trees were harvested either as delimbed stemwood or whole trees. The calculation was made for a hypothetical plant located in Central Finland and the radius of the procurement area was 100 km via the existing road network. Cutting was done with conventional harvester head equipped with multi-tree-handling (MTH) accessories, with the logged trees being chipped at the roadside stora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 26 publications
0
33
0
1
Order By: Relevance
“…The area that an NFI sample plot represents in a certain municipality and stand development class was calculated according to the methodology described by Laitila et al (2010a). The minimum yield of delimbed stems was set to be 25 m 3 ha -1 and average size of delimbed stems was greater than 20 litres on selected stands.…”
Section: Harvesting Conditions and Estimation Of The Potential Supplymentioning
confidence: 99%
See 1 more Smart Citation
“…The area that an NFI sample plot represents in a certain municipality and stand development class was calculated according to the methodology described by Laitila et al (2010a). The minimum yield of delimbed stems was set to be 25 m 3 ha -1 and average size of delimbed stems was greater than 20 litres on selected stands.…”
Section: Harvesting Conditions and Estimation Of The Potential Supplymentioning
confidence: 99%
“…Forwarding productivity was calculated by means of the model by Kuitto et al (1994). The payload (Table 3) was set in line with the work of Laitila et al (2010a). The gross effective time (E 15 h) coefficients (Table 3) for multi-stem cutting and forwarding were based on research by Jylhä et al (2010).…”
Section: Productivity and Cost Parameters Of The Procurement Systemmentioning
confidence: 99%
“…The models are based on a medium-size forwarder. We specified the load size to 6 m 3 for whole trees, and 9 m 3 for stemwood (pulpwood and delimbed stems), respectively (Laitila et al 2010;Laitila and Väätäinen 2011). To acquire the gross effective-time productivity (E15), we multiplied the effective-time productivity (E0) with 1.393 and 1.302 in harvesting and forwarding, respectively, as suggested by Laitila and Väätäinen (2011).…”
Section: Estimating Incomes Costs and Financial Performancementioning
confidence: 99%
“…This integrated harvesting generally reduces procurement costs of small-diameter wood (Rummukainen et al 2003;Kärhä 2011;Petty and Kärhä 2014), and for instance Heikkilä et al (2009) found the total stand management to be more profitable with integrated first thinning than with whole-tree first thinning in young pine or spruce stands. Whole-tree harvesting, where all trees including branches and tops are considered energy wood, may decrease the costs of cutting (no delimbing) but, on the other hand, increase the cost of forwarding due to the decreasing load size (Laitila et al 2010;Laitila and Väätäinen 2012). Preliminary studies concerning downy birch stands on drained peatlands have also shown that whole-tree energy wood harvesting, especially, may have poor profitability (Kojola et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Of these assortments, the supply costs of small trees are the highest because there is an additional cost of felling compared to the supply of crown biomass or sub-quality stemwood. Obtaining a supply of stump biomass also involves the additional cost of pulling the stumps out of the ground, but this is typically lower than the cost of felling small trees (Laitila et al 2010). Crown biomass, stumps and sub-quality stemwood are by-products of harvesting industrial roundwood, whereas small trees can be procured either in separate operations or as integrated with the pulp wood supply.…”
Section: Introductionmentioning
confidence: 99%